The creative economy in Mexico: Oaxaca’s case - Matadamas Torres, Lorenzo Alejandro; Regino Maldonado, Juan; Cruz Cabrera, Blasa Celerina; Castillo Leal, Maricela; Hernández Mendoza, Veronica (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2018)
Since the 2000s, in developing as well as developed countries, the subject of creative economy in economic development and growth has been relevant. In Mexico, studies in this regard are extremely important in marginalized states where creative and cultural activities contribute to regional economic development and strengthen the cultural ties and identity of indigenous peoples. The article proposes a model of creative economy for Mexico starting in Oaxaca, in addition to revealing its economic contribution to the state. First, scientific articles on creative economy published in scientific databases from 2000 to 2018 were reviewed. Next, the creative and cultural economic units, their generated jobs and their contributions to the GDP of the state production were identified.